Literature Review : Benefits of the essential oil content in green betel leaves (Piper Betle L) as anti-bacterial - Nurul Nubuwwah, Andi; Badli Rompegading, Andi; Fitriani, Fitriani; Shazirah Irfan, Nadia (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
Green betel leaf is a traditional medicine that contains essential oils and components consisting of kavicol, phenol, hydroxycavicol and several derivatives which act as antibacterials. The essential oil content in green betel leaves has anti-bacterial activity against various types of bacteria with a measure of its inhibitory power. The method used by researchers is literature review or literature review. The aim of this research is to determine the benefits of the essential oil content in green betel leaves ( Piper betle L ) as an anti-bacterial. The solutions used in several studies to extract essential oil content are; Aquades, Phenol, Methanol, Aquades, N-Hexane, Ethanol, and Ethylacetate, NaCl 0.85%, Ethanol 96%, Aquadest, Ethanol, DMSO 20%, and ethylacetate, which are used to inhibit bacteria. There are a number of factors that can influence literature review research regarding the benefits and essential oil content of green betel leaves (piper betle L).